Two new species of the genus Reticuluma Cheng & Li (Hemiptera: Cicadellidae: Deltocephalinae: Penthimiini) from China - Wang, Dongming; Zhang, Yalin (Zootaxa, 2019)
Two new species of the leafhopper genus Reticuluma: R. lageniformia and R. hamata spp. nov., are described and illustrated from China. A checklist and a key to the known species of Reticuluma are provided.